Clinico-Laboratory Observations and Outcome of Dengue Infection In a Tertiary Care Hospital of Western Nepal: An Observational Cross-Sectional Study - Jaiswal, Niraj Kumar; Chaudhary, Shatdal; Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Dengue fever (DF) is highly prevalent in tropical and subtropical countries all over the world. This study was done to study the clinico-laboratory profile of DF patients and their outcomes in a tertiary care hospital of western Nepal. MATERIAL & METHODS: A prospective observational cross-sectional study conducted over 6 months (October 2016 to March 2017) in patients admitted to medical inpatient ward of a tertiary care referral hospital located at south west Nepal. All febrile patients underwent dengue antibody (IgM) testing. Patient details, clinical manifestations and laboratory parameters were recorded. Descriptive analysis was done as mean and percentage. RESULTS: Out of total 2653 hospital admissions, 1274 patients (male: 780, female: 494) presented with fever. Forty patients between 17 years to 84 years (Mean age ± SD: 40.3±17 years) were diagnosed as DF. All the age groups were almost equally affected. The average duration of hospital stay was 5.4±3.2 days. Fever (n=40, 100%), body ache (n=29, 74.4%) and headache (n=28, 70%) were three leading complaints in dengue patients. Only 22.5% (n=9) of the patients had thrombocytopenia (mild and moderate). Severe thrombocytopenia was not noticed. Only 10% of total dengue cases received platelet transfusion. The mean platelet count increased from day one to day seven gradually. All the patients recovered. CONCLUSION: DF is a well-established vector-borne disease in south west Nepal; may be due to rapid urbanization and poor hygiene facility. Appropriate disease control programme emphasizing on vector surveillance and control, early clinical diagnosis and treatment reduces the dengue-related deaths. Journal of Universal College of Medical Sciences (2017) Vol.05 No.02 Issue 16, page: 3-7